A computational introduction to programming, mathematical modeling, and elementary mechanics - Freudenthal, E.; Roy, M.K.; Ogrey, A.; Siegel, A.; Gates, A.Q. (2009 39th IEEE Frontiers in Education Conference, 2009)
In Fall 2007, the Computer Science Department of the University of Texas at El Paso introduced a media-centric introductory programming course informally titled "Computational Computer Science Zero" (CCS-0) for incoming freshmen with weak mathematics preparation. These students typically have to spend several semesters in preparatory math courses before enrolling in the major's first course. CCS-0 is intended to circumvent this delayed entry into STEM subjects by offering an accessible, enticing introduction to physical modeling and computational science. The main curriculum objectives are to exploit introductory programming as a vehicle for strengthening student intuition and confidence in pre-calculus concepts via hands-on simulation of physical phenomena, and thereby stimulate interest in more advanced study within these technical areas. This paper describes the structure of CCS-0 including an overview of its organization, expected outcomes and example problems that model ballistics and resonant systems. The evaluation plan is described and early results are presented.